Indonesia‘s Public Diplomacy Strategy through Instagram @kemlu-ri in Shaping a Positive Image in ASEAN (2020-2024) - Khoirul Prasetio; Made Santoso (Universitas Negeri Yogyakarta, 2026)
Abstract This study examines Indonesia’s digital public diplomacy strategy through the official Instagram account @kemlu_ri in shaping a positive image in the ASEAN region during the 2020–2024 period, focusing on the effectiveness of the Ministry of Foreign Affairs’ communication amid the COVID-19 pandemic, geopolitical competition, and digital transformation in Southeast Asia. The study uses a qualitative descriptive-analytical approach and applies content analysis (visuals, narratives, and audience engagement) as well as discourse analysis to examine diplomatic messages and framing, drawing data from ASEAN-related Instagram posts, official documents, media coverage, and academic literature through source triangulation. The findings show that @kemlu_ri functions not only as a channel for foreign policy information but also as an instrument for positive image-building that highlights cultural identity, diplomatic contributions, and Indonesia’s active role in maintaining ASEAN centrality, which strengthens Indonesia’s soft power despite challenges in message consistency and audience reach. Theoretically, this study contributes to digital diplomacy scholarship by advancing the understanding of digital public diplomacy through the integration of visual and discourse analysis of social media as a mechanism for state image construction at the regional level.